The impact of song-specific age and affective qualities of popular songs on music-evoked autobiographical memories (MEAMs) - Platz, Friedrich; Kopiez, Reinhard; Hasselhorn, Johannes; Wolf, Anna (Musicae Scientiae, 2015)
Songs heard between the ages of 15 and 24 should be remembered better and have a stronger relationship to autobiographical memories when compared with music from other phases of life (“reminiscence bump effect”). Additionally, the proportion of music-evoked autobiographical memories (MEAMs) is at a maximum in these years of early adolescence and then declines up to the age of 60. In our study we tried both to replicate these important findings based on a German sample and to further investigate the influence of the affective characteristics of the songs on the frequency of participants’ autobiographical memories. In Experiment 1 a group of adults (N = 48, Mage = 67.1 years) listened to excerpts from 80, number-one, popular music hits from 1930 to 2010 and gave written self-reports on MEAMs. In Experiment 2 the affective characteristics were rated by another group of adults (N = 22, Mage = 66 years) and were used to predict the frequency of MEAMs. As a main result of Experiment 1, we confirmed the reminiscence bump and decline effect with a small effect size for the ratings of feelings evoked by the song and with a medium effect size for the song recognition performance of those songs released during the participants’ age range of 15 to 24 years. The total number of MEAMs was only marginally influenced by a memory bump and decline effect, and participants showed a significant proportion of MEAMs up to the fifth decade. Experiment 2 revealed that the affective ratings of the songs were unequally distributed over the two-dimensional emotion space unlike the average rate of MEAMs which was nearly equally distributed. In contrast to previous research, we therefore conclude that popular songs can be associated with autobiographical memory over five decades of life – independent of the affective character of the music.
CRIS-Team Scopus Importer:2023-03-21
Keywords: arousal; music-evoked autobiographical memory; popular music; reminiscence bumb effect; song-specific age; valence